2022
DOI: 10.1136/bmjopen-2022-060937
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wheelchair falls in team sports at the Paralympic Games: video-based descriptive comparison between the Rio 2016 and Tokyo 2020 games

Abstract: ObjectivesTo identify the fall characteristics of athletes in wheelchair rugby and wheelchair basketball during the Tokyo 2020 Paralympic Games and descriptively compare these with those of the Rio 2016 Paralympic Games.DesignCross-sectional analysis.Primary and secondary outcome measuresWe obtained video footage from the International Paralympic Committee of the Tokyo 2020 Paralympic Games that included 8 teams from each of the 18 wheelchair rugby and 10 wheelchair basketball games (men and women). The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Such technology advancement may be seen as unfair ( 136 ) and the potential technological advantage for a Paralympian, when competing against an Olympian, is unclear ( 137 ). However, beyond performance, the innovation is also for improving safety ( 138 ) with a direct impact for the stability/safety of equipment used daily by disable individuals ( 139 ), potentially bringing to the latter a substantial improvement of their quality of life.…”
Section: Dose-response To Exercisementioning
confidence: 99%
“…Such technology advancement may be seen as unfair ( 136 ) and the potential technological advantage for a Paralympian, when competing against an Olympian, is unclear ( 137 ). However, beyond performance, the innovation is also for improving safety ( 138 ) with a direct impact for the stability/safety of equipment used daily by disable individuals ( 139 ), potentially bringing to the latter a substantial improvement of their quality of life.…”
Section: Dose-response To Exercisementioning
confidence: 99%
“…Sasadai et al 14 reported that the number of falls during men’s wheelchair basketball games was approximately 1.9 times higher than that in women’s games. In a follow-up report, Fukui et al 15 compared the characteristics of falls in wheelchair team sports at the Rio 2016 and Tokyo 2020 Paralympic games. However, two major concerns were associated with these studies.…”
mentioning
confidence: 99%